Effect of subthalamic coordinated reset deep brain stimulation on Parkinsonian gait - Bosley, Kai M.; Luo, Ziling; Amoozegar, Sana; Acedillo, Kit; Nakajima, Kanon; Johnson, Luke A.; Vitek, Jerrold L.; Wang, Jing (Frontiers in Neuroinformatics, 2023)
Coordinated Reset DBS (CR DBS) is a novel DBS approach for treating Parkinson's Disease (PD) that uses lower levels of burst stimulation through multiple contacts of the DBS lead. Though CR DBS has been demonstrated to have sustained therapeutic effects on rigidity, tremor, bradykinesia, and akinesia, following cessation of stimulation, i.e., carryover effect, its effect on parkinsonian gait has not been well studied. Impaired gait is a disabling symptom of PD often associated with higher risk of falling and reduced quality of life. The goal of this study was to explore the carryover effect of subthalamic CR DBS on parkinsonian gait. Three non-human primates (NHPs) were rendered parkinsonian and implanted with a DBS lead in the subthalamic nucleus (STN). For each animal, STN CR DBS was delivered for several hours per day across 5 consecutive days. A clinical rating scale modified for NHP use (mUPDRS) was administered every morning to monitor the carryover effect of CR DBS on rigidity, tremor, akinesia and bradykinesia. Gait was assessed quantitatively before and after STN CR DBS. The stride length and swing speed were calculated and compared to the baseline, pre-stimulation condition. In all three animals, carryover improvement in rigidity, bradykinesia, and akinesia were observed after CR DBS. Increased swing speed was observed in all the animals, however, improvement in stride length was only observed in NHP B2. In addition, STN CR DBS using two different burst frequencies was evaluated in NHP B2 and differential effects on the mUPDRS score and gait were observed. Although preliminary, our results indicate that STN CR DBS can improve parkinsonian gait together with other motor signs when stimulation parameters are properly selected. This study further supports the continued development of CR DBS as a novel therapy for PD and highlights the importance of parameter selection in its clinical application.